Necrotizing fasciitis and sepsis caused by Vibrio vulnificus and Klebsiella pneumoniae in diabetic patients - Jiun-Cheng Hsu; Shih-Hsun Shen; Tien-Yu Yang; Po-Han Chen; Kuo-Chin Huang; Yao-Hung Tsai (Biomedical Journal, 2015)
Background: Vibrio vulnificus related necrotizing fasciitis is a fatal, rapidly progressive soft-tissue infection. Necrotizing fasciitis caused by Klebsiella pneumoniae is rare, which is indistinguishable from V. vulnificus infection in the emergency room. The purpose of this study was to compare the clinical characteristics and outcome between these two pathogens in diabetic patients. Methods: Thirty diabetic patients were retrospectively reviewed over an 8-year period. Necrotizing fasciitis caused by V. vulnificus was found in 19 patients and by K. pneumoniae in 11 patients. The demographic, clinical, and laboratory characteristics, and the outcome between diabetic patients with V. vulnificus and K. pneumoniae infections were compared. Results: Two patients in the V. vulnificus group (10.5%) and three patients in the K. pneumoniae group (27.3%) died. Fourteen patients in the V. vulnificus group (73.6%) had a history of exposure to seawater or raw seafood, and eight patients in the K. pneumoniae group (72.8%) had abrasions or chronic ulcers over the site of infection. We found that the time interval between onset of illness and presentation to the hospital was significantly shorter in the V. vulnificus group than in the K. pneumoniae group (2.47 days vs. 5.45 days, p < 0.001). Conclusions: The exposure history and the time from exposure to hospital presentation with severe sepsis syndromes should alert clinicians to distinguish between necrotizing soft-tissue infections with V. vulnificus (contact with seawater or raw seafood) and K. pneumoniae (abrasions or chronic ulcers) in diabetic patients. Infection with V. vulnificus progresses more rapidly than infection with K. pneumoniae during the initial clinical course.